Healthcare priorities: the "young" and the "old" - Davies, BT (Cambridge University Press, 2022)
Some philosophers and segments of the public think age is relevant to healthcare priority-setting. One argument for this is based in equity: “Old” patients have had either more of a relevant good than “young” patients or enough of that good and so have weaker claims to treatment. This article first notes that some discussions of age-based priority that focus in this way on old and young patients exhibit an ambiguity between two claims: that patients classified as old should have a low priority, and that patients classified as young should have high priority. The author next argues, drawing on a problem raised by Christine Overall, that equity cannot justify giving “old” patients low priority, since there is wide variety in the total lifetime experiences of older people, partly influenced by gender, race, class, and disability injustice. Finally, the author suggests that there might be a limited role for age-based prioritization in the context of infant and childhood death, since those who die in childhood are always and uncontroversially among the worst-off.